2015
DOI: 10.1002/elsc.201400127
|View full text |Cite
|
Sign up to set email alerts
|

Role of copper and iron in methane oxidation and bacterial biopolymer accumulation

Abstract: The aim of this review was to elucidate the role of copper and iron in regulating methane (CH4) oxidation and subsequent biopolymer (i.e. polyhydroxyalkanoate [PHA]) accumulation in methanotrophic bacteria. Specifically, the review emphasizes the “copper switch mechanism” that alters CH4 oxidizing enzyme activities, that is soluble‐ and particulate methane monooxygenases, in type II methanotrophic bacteria. Both copper and iron are essential nutrients and reports demonstrate that addition of either can improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…Prior research has shown that the expression of MMOs is regulated by Cu 2+ . To be more accurate, the expression of sMMO is efficient at less than 0.8 μM Cu 2+ and is restricted at an excess of 4 μM of Cu 2+ in methanotrophs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that the expression of MMOs is regulated by Cu 2+ . To be more accurate, the expression of sMMO is efficient at less than 0.8 μM Cu 2+ and is restricted at an excess of 4 μM of Cu 2+ in methanotrophs .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the expression of pmoA and mmoX, the quantity of pmoA was 1 to 4 orders of magnitude greater than that of mmoX, indicating that pMMO likely plays a more prominent role than sMMO under these conditions. Prior research has shown that the expression of MMOs is regulated by Cu 2+ [13,16,17]. To be more accurate, the expression of sMMO is efficient at less than 0.8 μM Cu 2+ and is restricted at an excess of 4 μM of Cu 2+ in methanotrophs [38].…”
Section: Expression Of Pmoa and Mmox At Different Cu 2+ Concentrationsmentioning
confidence: 99%
“…Recent attention has been paid to the optimization of PHB accumulation from a microbiological point of view by identifying the key limiting macro/micronutrients that boost PHB synthesis in methanotrophs. However, to the best of the authors' knowledge, the influence of micronutrients such as Mn, Fe, and K on methanotrophic PHB synthesis has been scarcely studied [18,19]. Moreover, few studies have evaluated the simultaneous abatement of dilute CH 4 emissions and co-production of PHB in gas-phase bioreactors under continuous operation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous microelements have been established or are newly emerging as control points for primary methane oxidation ( Glass and Orphan, 2012 ; Chidambarampadmavathy et al, 2015 ; Semrau et al, 2018 ). Three key metabolic switches have been described: (1) a copper-switch, which controls the expression and activity of primary methane oxidation ( Stanley et al, 1983 ; Semrau et al, 2018 ); (2) a tungsten-molybdenum (W/Mo) switch for formate oxidation ( Laukel et al, 2003 ; Chistoserdova et al, 2004 ; Akberdin et al, 2018 ); and (3) a La-switch, which negatively regulates the expression of MxaFI-MeDH and activates XoxF-MeDH ( Haque et al, 2015 ; Chu and Lidstrom, 2016 ; Chu et al, 2016 ; Gu and Semrau, 2017 ; Semrau et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%